A direct costing system for the street food segment - Pigatto, Gessuir; Machado, Joao Guilherme de Camargo Ferraz; Queiroz, Timoteo Ramos; Nishimura, Julian Roberto [UNESP]; Dos Santos, Andrei Golfeto [UNESP] (My University, 2016)
Current research develops a system of direct costing for the street food segment, especially for street food vendors by identifying costs for abetter management of working capital and competitiveness in business. Current exploratory and descriptive research identifies the main factors used in street food and proposes a simplified model for costs from the entrepreneurs' point of view. Methodology comprised two procedures. The first procedure involved five entrepreneurs to fill the worksheet by a transversal collection; the second procedure comprised an entrepreneur from Tupa SP Brazil who longitudinally filled the cost sheet for 4 weeks.
Keywords: Competitiveness; Costing system; Direct costing; Entrepreneurs; Street food